Subclinical ketosis in postpartum dairy cows alters the adipose tissue immunological profile in a depot-specific manner - Michelotti, Tainara C.; Menarim, Bruno C.; Tegeler, Alexandra P.; Fiallo Diez, Jean F.; Machado, Vinicius S.; Jones-Hall, Yava; Benitez, Oscar J.; Loux, Shavahn C.; Strieder-Barboza, Clarissa (Frontiers in Immunology, 2025)
IntroductionSubclinical ketosis (SCK) is a common metabolic disorder linked to adipose tissue (AT) dysfunction in periparturient dairy cows. While subcutaneous AT (SAT) and visceral AT (VAT) differ in structure, cellularity, and function, depot-specific responses to ketosis remain poorly understood. This study aimed to determine the transcriptional differences of flank SAT and omental VAT in early lactation dairy cows in response to SCK.MethodsMultiparous Holstein dairy cows within the first 10 days postpartum were screened for SCK. Subclinical ketosis was defined as blood β-hydroxybutyrate (BHB) concentrations between 1.4 and 2.6 mmol/L, while control, non-ketotic animals (NK) had BHB equal to or lower than 0.8 mmol/L. Adipose tissue biopsies were obtained from flank SAT and omental VAT from five SCK and five NK cows for RNA sequencing and immunohistochemistry analyses.Results and DiscussionSubclinical ketosis affected AT transcriptional profiles in a depot-specific manner. In SAT, transcriptional changes related to SCK reflected homeostatic AT remodeling and immune cell infiltration indicative of inflammatory responses, fibroplasia, and the negative regulation of adaptive immunity responses. In VAT, SCK-related transcriptional changes reflected increased pro-inflammatory responses linked to impaired lipid metabolism and dysregulation of focal adhesion and endocytosis. Tissue expression of proteins coded by genes differentially expressed between SCK and NK revealed a depot-dependent response on AT, indicating a higher infiltration of macrophages and B cells in SCK cows. Overall, our study provides new insights into molecular mechanisms underlying ketosis pathogenesis, highlighting the dysregulation of inflammatory responses, lipid metabolism, and insulin signaling in both SAT and VAT of postpartum dairy cows.